EPIDEMIC CORRUPTION: A BIO-ECONOMIC HOMOLOGY - Salem Hathroubi; Hedi Trabelsi (European Scientific Journal, ESJ, 2014)
This paper aims to study corruption as an epidemic phenomenonusing the epidemic diffusion model of Kermack and Mc-Kendrick (1927).We seek to determine the dynamics of corruption and its impact on thecomposition of the population at a given time. We determine a thresholdepidemiological corruption based on the approximation of the honestpopulation.